Implementation of Character Education for Students in Pandemic Covid-19 - Salsabila, Febby; Putri, Riski Ananda (LPPI Yayasan Almahmudi bin Dahlan, 2023)
Character education is an action or effort in applying useful character values for students that can b from science with the help of an educators such US parents, teachers, lectures, etc . this study aims to determine how character education for students of Junior Highschool 3 Bangkinang during the covid-19 pandemic. this research used a qualitative descriptive method. This source came from five teachers in Junior high school 3 Bangkinang. Research data is taken through direct interviews with all informants. the results showed that character education is very important for a child to have, especially during the covid-19 pandemic. character education can b obtained through 2 processes. First, in the learning process the teacher develops characters such as a syllabus or leeon plan. Second, character education is carried out outside of compulsory learning such as taking extracurricular activities in school US self-development. in character education there are 18 characters that must be possessed by religious values, discipline, creative, fond of reading curiosity, honestly, caring for the environment, responsibility, hard work, friendly homeland love, caring, respect, democracy, tolerance, the spirits of nationalism and love peace.